Production Process of Front Lights on Anoa 2 6x6 Special Vehicles at PT. Pindad (Persero) - Abdul Khair Junaidi; Nandha Syamza; Tri Subagyo (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
The headlights on Anoa 2 6x6 special vehicles are used for street lighting for anoa tanks at night. The purpose of this study was discussed the steps of production process of the Anoa 2 6x6 headlights in PT. Pindad. The headlight component was made in several manufacturing processes that were carried out. It consists of many parts, which a variety of production machines for the manufacture of each part. The manufacturing of the headlight components using machining processes such as laser cutting, welding, and drilling. The type of material used for the manufacture of the headlights and parts that was Aluminum Alloy 2044 and Steel ST-37. The result components were made the headlight frame, BT protectors, the front, side, and rear components.